Chd4 and associated proteins function as corepressors of Sox9 expression during BMP‐2–induced chondrogenesis. (19th August 2013) - Sun, Fenyong; Yang, Qingyuan; Weng, Wenhao; Zhang, Yue; Yu, Yongchun; Hong, An; Ji, Yuhua; Pan, Qiuhui
ABSTRACT: Mouse embryonic fibroblasts (MEFs) differentiate into fully functional chondrocytes in response to bone morphogenetic protein‐2 (BMP‐2). However, the comprehensive proteomic aspect of BMP‐2–induced chondrogenesis remains unknown. We took advantage of quantitative proteomic analysis based on isobaric tag for relative and absolute quantitation (iTRAQ) and on‐line 2D nano‐liquid chromatography/tandem mass spectrometry (LC/MS/MS) to identify proteins differentially expressed during BMP‐2–induced chondrogenic differentiation of MEFs. We found 85 downregulated proteins, and ingenuity pathways analysis (IPA) revealed a protein‐protein network with chromodomain‐helicase‐DNA‐binding protein 4 (Chd4) in the center. Chromatin immunoprecipitation (ChIP) and nuclease hypersensitivity assays showed that Chd4, interacting with Hdac1/2, cooperates with its related proteins Kap1 and Cbx1 to bind at −207/−148 of the Sox9 promoter. We also provided evidence that let‐7a targets the 3'UTR of Chd4 to promote chondrogenesis of MEFs. Together, our findings indicate that BMP‐2 induced the upregulation of let‐7a, targeting Chd4 and positively controlling the chondrogenic differentiation of MEFs. These findings illustrate epigenetic regulation of the chondrogenic differentiation process and also expand the understanding of the involved intracellular mechanisms.